Operational Risk Management On The Training Ship Bung Tomo - Pribadi, Teguh; Dwi Santoso, Agus; Harianto, Bambang Bagus (Technium Social Sciences Journal, 2023)
Risk management plays a crucial role in ensuring the sustainability of an organization’s operations. At the Surabaya Navigation Polytechnic, Bung Tomo’s training vessel became the backbone for cadets to undergo navigation training. However, it is important to acknowledge that the ship’s operational activities are not exempt from potential risks. Therefore, the study aims to identify potential obstacles or issues that may arise in the implementation of risk management at the Tomo Training Ship. This research adopts a qualitative descriptive approach, prioritizing an in-depth understanding of the observed phenomena. Various data collection techniques, such as observations, interviews, and documentation, are used to gain comprehensive insights. The results of this study reveal that the Engine of Tomo’s Training Ship faces the highest level of risk. It’s related to the fact that the ship hasn’t undergone a major dock process since it was officially inaugurated six years ago, causing frequent damage. Therefore, risk management focused on the engine aspects becomes an urgent need to minimize potential interference in ship operations. Precautionary measures, periodic maintenance, and possible risk reduction must be implemented carefully to ensure the safety and reliability of the Tomo Brother’s Training Ship during the cadets’ sailing training.